The effect of pH on the simultaneous determination of Sulfamethoxazole and Trimethoprim by Ultraviolet Spectrophotometry and Multivariate Calibration - E.B. da Silva, Fabiana; R.R. Almeida, Willian; R. Paula, Fávero; L.H. Müller, Aline; M.M. Flores, Érico; F Ferrão, Marco (Drug Analytical Research, 2026)
Analytical techniques based on Ultraviolet (UV) spectrophotometry are widely used in pharmaceutical analysis, because they are simple and inexpensive. The choice of pH is critical in the development of univariate methods for pharmaceutical quantitation by UV spectrophotometry since changes may modify the absorption spectrum profile. Similar to univariate methods by UV spectrophotometry changes in pH may influence the predictive ability of multivariate models, affecting the resultant analytical performance. We report herein on the influence of pH on the simultaneous determination of sulfamethoxazole (SMZ) and trimethoprim (TMP) in tablets using UV spectrophotometry and multivariate calibration. Data were recorded using a UV spectrophotometer in the wavelength range of 200 to 350 nm. The experimental matrix was constructed using 36 synthetic samples of SMZ-TMP mixtures. The concentration ranges used for the investigation were 14.0 to 26.0 mg L-1 for SMZ and 2.8 to 5.2 mg L-1 for TMP. The Partial Least Squares (PLS) regression models were generated with full-spectrum and multiple pH levels. At pH 4.3, lower values of relative standard error of prediction (RSEP %) for SMZ (1.83) and TMP (1.13) were obtained. The PLS model at pH 4.3 was used for the quantification of real samples (tablets obtained from 13 different manufacturers) and the results were compared with conventional procedures using high performance liquid chromatography (HPLC).